Environmental aspects of ecosystem restoration: development and application of nanocarbon sorbents (Environment & Health, 2025)
To summarize existing approaches to the treatment of polluted water containing nanoparticles with adsorbed pollutants of various origins, and to develop and apply nanocarbon-based sorbents and nanocomposites for effective purification of such waters.Materials and Methods: Model systems included natural water and a simulated polluted solution containing organic substances (humates, organic acids, detergents, crude oil), heavy metals (Sr, Co, Mn, Fe), and nitrates. Sorbents were synthesized using natural graphite modified with sulfuric acid, bentonite clay, and micro- and nanoparticles of metallic iron and its oxides. Nanocomposites were produced through mechanochemical activation and microwave treatment. Morphological, dimensional, and structural properties of the particles were studied using scanning electron microscopy (SEM), X-ray diffraction (XRD), and laser sedimentation. The concentrations of metals and organic substances in the solutions were determined using atomic absorption spectrophotometry and chemical oxygen demand (COD) by dichromate oxidation, respectively.Results: Military actions in Ukraine since 2022 have led to environmental deterioration due to the influx of pollutants, particularly nanoparticles, which are highly toxic and pose risks to ecosystems and human health. The developed sorbents based on thermally expanded graphite and high-dispersity aluminosilicates proved effective in removing a wide range of pollutants. The synthesized magnetosensitive nanocomposite achieved significant purification efficiency: a 10–15-fold reduction in organic contaminant concentration, with removal efficiencies of ~94% for cobalt, >98% for manganese and iron, and ~92% for strontium.Conclusions: The findings confirm the feasibility of using nanocomposites based on thermally expanded graphite and bentonite for targeted removal of complex pollutant mixtures from aqueous environments. The proposed approaches offer a promising basis for new technologies in the treatment and regeneration of technogenically polluted waters in areas of anthropogenic impact.
Keywords: nanocomposite; thermally expanded graphite; heavy metals; organic pollutants